Transmembrane Calcium Influx Associated with von Willebrand Factor Binding to GP Ib in the Initiation of Shear-Induced Platelet Aggregation - Ikeda, Yasuo; Handa, Makoto; Kamata, Tetsuji; Kawano, Koichi; Kawai, Yohko; Watanabe, Kiyoaki; Kawakami, Keiko; Sakai, Kiyotaka; Fukuyama, Mayumi; Itagaki, Ichiro; Yoshioka, Akira; Ruggeri, Zaverio M (Thrombosis and Haemostasis, 1993)
We found that the binding of multimeric vWF to GP Ib under a shear force of 108 dynes/cm2 resulted in the transmembrane flux of Ca2+ ions with a two-to three-fold increase in their intracellular concentration ([Ca2+]i). The blockage of this event, obtained by inhibiting the vWF-GP Ib interaction, suppressed aggregation. In contrast, the blockage of vWF binding to GP IIb-IIIa, as well as the prevention of activation caused by increased intracellular cAMP levels, inhibited aggregation but had no significant effect on [Ca2+]i increase. A monomeric recombinant fragment of vWF containing the GP Ib-binding domain of the molecule (residues 445-733) prevented all effects mediated by multimeric vWF but, by itself, failed to support the increase in [Ca2+]i and aggregation. These results suggest that the binding of multimeric vWF to GP Ib initiates platelets aggregation induced by high shear stress by mediating a transmembrane flux of Ca2+ ions, perhaps through a receptor-dependent calcium channel. The increase in [Ca2+]i may act as an intracellular message and cause the activation of GP IIb-IIIa; the latter receptor then binds vWF and mediates irreversible aggregation.